Pasteurella multocida Bacteremia in a Patient with Diabetic Foot Infection (Bangladesh Journal of Medical Science, 2017)
Human infection by Pasteurella multocida is commonly associated with cat or dog bite. This is the case report of a 57-year-old lady with chronic diabetes mellitus and hypertension presented with non-healing left leg ulcer for three weeks duration. A Pasteurella multocida bacterium was isolated in the Microbiology Laboratory from her blood specimen. Diagnosis and management of the patient are discussed.Bangladesh Journal of Medical Science Vol.16(3) 2017 p.474-476